Necesaria modificación de lege ferenda del artículo 400 del código civil para la protección eficaz del derecho a la identidad. P - Dionicio Méndez, Brenda Estefany (2023)
The investigation seeks to demonstrate that a modification of article 400 of the Civil Code is necessary, regarding the expiration period to be able to initiate an action to challenge extramarital paternity, since it violates the right to identity. In this sense, it remains in this thesis to propose a solution to the problem, but not any solution within the existing range of legal reality, but the most effective possible solution. Due to this, the thesis is based on the need to solve the conflict in which - in cases where the period for filing the paternity challenge claim has expired - incurs said legal norm (Article 400 of the civil code) contravening to the right to identity, since it establishes an expiration period to challenge the paternity of an extramarital child, limiting the enjoyment of the right to identity, which is related to other rights. Consequently, faced with the problem raised, the solution made by the Supreme Court corresponds to the non-application of the norm through diffuse control; however, it is not the most effective solution; being necessary the modification of lege ferenda of article 400 of the civil code; in order to protect the right to identity.